1991
DOI: 10.1111/j.1600-051x.1991.tb00439.x
|View full text |Cite
|
Sign up to set email alerts
|

An in vivo model for the identification of serum proteins in the acquired subgingival pellicle

Abstract: The present study describes an in vivo model for the collection of the subgingival pellicle adsorbed to tooth surface, and the identification of some serum proteins within this layer. Clean dentin slabs were prepared from freshly extracted teeth, and then placed subgingivally for 2 h. The dentin slabs with their adsorbed pellicle layer were processed for transmission electron microscopy. Thin sections were made from the specimens, and treated with antisera to human immunoglobulins and albumin. The reactions we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…In earlier reports, experimental pellicles formed on enamel from plasma alone or in combination with saliva, contained bands of plasma protein (22). Albumin was identified in the natural pellicle (9, 24) and, together with immunoglobulins, on dentine slabs exposed to the gingival crevicular fluid in vivo (1). In our previous studies, salivary high‐molecular‐weight glycoproteins, proline‐rich proteins and IgA were identified in pellicles formed on teeth and in experimental pellicles formed on hydroxyapatite from saliva (9, 32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In earlier reports, experimental pellicles formed on enamel from plasma alone or in combination with saliva, contained bands of plasma protein (22). Albumin was identified in the natural pellicle (9, 24) and, together with immunoglobulins, on dentine slabs exposed to the gingival crevicular fluid in vivo (1). In our previous studies, salivary high‐molecular‐weight glycoproteins, proline‐rich proteins and IgA were identified in pellicles formed on teeth and in experimental pellicles formed on hydroxyapatite from saliva (9, 32).…”
Section: Discussionmentioning
confidence: 99%
“…In the oral cavity, saliva is an important and thoroughly studied source of pellicle and plaque formation (for review, see 27). The role of the gingival crevicular fluid on dental biofilm formation has only been investigated to a limited extent (1, 31).…”
mentioning
confidence: 99%
“…Kobayashi and Rose (1979) noted that the DC was a layer composed of highly condensed protein, since it was completely digested with the proteolytic enzymes trypsin and protease. Previous studies have suggested that the structure consists of anionic polymers, including glycoproteins (Friedman et al, 1993), or serum proteins, mainly albumin, IgA, and IgG, in the gingival fluid (Eide et al, 1984;López et al, 1990;Abbas et al, 1991). In contrast, purified P. gingivalis fimbriae bound strongly to glyco-conjugates, such as albumin-fucosylamide, through lectin-like interaction with carbohydrate (Sojar et al, 2004).…”
Section: Discussionmentioning
confidence: 98%
“…In similar in vitro studies,it has been stated that effect of experimental pellicle was different from natural pellicle. 16,[25][26][27] The lack of enzymatic activity in vitro was found to be the reason for the difference, because this enzymatic activity plays an important role in pellicle adsorption and bacterial adhesion. 1,16,28 In this study, the method described by Wise & Dykema 29 and Nakazato et al 30 was used for pellicle and bacterial plaque formation.…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers showed both of these bacterial species to have specific receptors for salivary amylase and proline-rich proteins. [22][23][24][25][26][27][28][29][30][31][32][33][34][35] Edgerton et al 57 showed proline rich proteins and salivary amylase as precursor components for pellicle on titanium in vitro and those molecules might be responsible for in vivo adhesion of same bacteriae. In this study α-amylase was found on all of the surfaces except feldspathic porcelain.…”
Section: Discussionmentioning
confidence: 99%